Upaya Meningkatkan Hasil Belajar Matematika Menggunakan Metode Demonstrasi dengan Media Realia Materi Perkalian pada Siswa Kelas III SD Negeri 19 Rabangodu Utara Kota Bima - Sukmawati, Eti (Gravity Edu : Jurnal Pembelajaran dan Pengajaran Fisika, 2023)
His study aims to improve mathematics learning outcomes in multiplication material for third-grade students at SD Negeri 19 Rabangodu Utara, Kota Bima, through the demonstration method using realia media. The study employed a Classroom Action Research (CAR) approach conducted in two cycles. Each cycle consisted of planning, implementation, observation, and reflection. Data was collected through observation sheets and formative tests. The results showed a significant improvement in students' learning mastery. In Cycle I, the mastery level reached 56% with an average score of 62. However, in Cycle II, the mastery level increased to 96% with an average score of 95. This success was supported by the use of the demonstration method with realia media, which facilitated students' understanding of multiplication concepts, as well as enhanced their motivation and active engagement during the learning process. The study concludes that the demonstration method with realia media is effective in improving students' learning outcomes in mathematics. Therefore, this method is recommended for implementation in elementary school teaching, particularly for materials requiring concrete understanding